Enhancement of Desulfurization Process for Light Gas Oil Using New Zinc Oxide Loaded Over Alumina Nanocatalyst - Aabid, Ahmad Abdulsalam; Humadi, Jasim Ibrahim; Ahmed, Ghazwan Saleh; Jarullah, Aysar Talib; Ahmed, Mustafa Abdulbari; Abdullah, Waqas Saadi (Applied Science and Engineering Progress, 2023)
This work reports the removal of dibenzothiophene (DBT) via an oxidative desulfurization (ODS) process over Zn/Al2O3 catalyst utilizing H2O2 as an oxidizing agent. The influence of operating parameters, such as reaction temperature, time was investigated. Results clarified that recognizably high DBT elimination of 93.781% has been achieved within 80 min using 0.1 g (9% Zn/Al2O3) catalyst at 90 °C reaction temperature. It was observed that an overall ODS catalytic efficiency order of: 9% ZnO/γ-Al2O3> 6% ZnO/γ-Al2O3> 3% ZnO/γ-Al2O3. Discernment of the surface morphology and textural properties of prepared nano-catalysts were characterized utilizing X-ray diffraction (XRD), scanning electron microscopy (SEM), fourier transform infrared (FTIR) and BET surface area analysis, which assisted in evaluating the performance of the prepared nano-catalysts. Owing to its highly effective nature, operation at moderate conditions and cost-effectiveness, this work can be conceived as an efficient methodology for the ODS operation of fuel oils on an industrial scale.